Liderazgo pedagógico en el proceso de enseñanza aprendizaje de matemáticas de los estudiantes de primer año de Bachillerato General Unificado en el período lectivo 2024-2025. - Pogo Nole, Marbi Alexandra (2025)
This research addresses the issue of pedagogical leadership of the teacher in the teaching-learning process of mathematics for first-year students of Unified General Baccalaureate during the 2024- 2025 academic year. Its purpose is to strengthen teacher performance and improve learning in this subject. The study, of a documentary and descriptive nature, uses scientific methods, bibliographic review, and techniques such as filing and surveys to gather relevant information. The findings highlight that the implementation of innovative methodological strategies and pedagogical leadership techniques promotes the critical, reflective, and analytical development of students, contributing to meaningful and dynamic learning. As a proposal, a practical guide is suggested that integrates these strategies adapted to teaching.